Comparative study with sheep and goats of the digestibility of a native legume in the semi-arid zone of Ceará, Brazil. II. In vivo digestibility of the silage of Cassia sp. - Barros, Nelson Nogueira; Kawas, Jorge R.; Lopes, Expedito Aguiar; Johnson, William L. (Pesquisa Agropecuaria Brasileira, 1992)
Ten SRD (undefined genotype) goats and ten sheep of the Santa Inês getiotypes, were used to evaluate the nutritive value of the mata-pasto (Cassia spp) silage. Experimental animals were kept in elevated metabolism crates for a 14-day adaptation period followed by a 7-day collection period of total faeces. All animals were adult males and castrated and they were given ad libitum access to water, mineral salt and forage consumption. There was no significant (PL0,05) difference between goat and sheep for any of the studied variables. Crude protein (CP), neutral detergent fiber (NDF) and KMnO lignin contents of the mata-pasto silage were, respectively, 7.0, 55.3 and 7.8%. Intake of dry matter and of digestible organic matter were, respectively, 72.0 and 43.0 g/kg0,75/day for goats and 86.8 and 53.8 g/kg0,75/day for sheep. NDF and dry matter digestibilities were in the order, of 60.1 and 60.4% and 43.0 and 44.6% for goats and sheep, respectively. Total chewing time was 925 min/day for goats and 990 min/day for sfteep. Both animal species showed similar feed utilization eficiency.